Compactness in normed spaces: a unified approach through semi-norms - Gulgowski, Jacek; Kasprzak, Piotr; Maćkowiak, Piotr (Topological Methods in Nonlinear Analysis, 2023)
In this paper we prove two new abstract compactness criteria in normed spaces.To this end we first introduce the notion of an equinormed set using a suitable family of semi-norms on the given normed space satisfying some natural conditions. Those conditions, roughly speaking, state that the norm can be approximated(on the equinormed sets even uniformly) by the elements of this family. As we are given some freedom of choice of the underlying semi-normed structure that is used to define equinormed sets, our approach opens a new perspective for building compactness criteria in specific normed spaces. As an example we show thatnatural selections of families of semi-norms in spaces $C(X,\R)$ and $l^p$ for$p\in[1,+\infty)$ lead to the well-known compactness criteria (including theArzel\`a-Ascoli theorem). In the second part of the paper, applying the abstract theorems, we construct a simple compactness criterion in the space of functions of bounded Schramm variation.